First isolation of Leishmania infantum by blood culture in bovines from endemic area for canine visceral leishmaniasis - Paixão-Marques, Mirian Dos Santos [UNESP]; Alves-Martin, Maria Fernanda [UNESP]; Guiraldi, Lívia Maísa [UNESP]; Dos Santos, Wesley José [UNESP]; De Lemos, Fábio Almeida [UNESP]; Sánchez, Gabriela Pacheco; Richini-Pereira, Virginia Bodelão; Lucheis, Simone Baldini [UNESP] (Cambridge University Press (CUP), 2019)
Leishmaniasis is considered a parasitic disease that still causes serious consequences for mankind, because it presents a high mortality rate worldwide. Considered multi-hosts, the parasites of the genus Leishmania are able of infecting a wide variety of animal species. The dog was considered the main source of infection of visceral leishmaniasis (VL), in the urban area. However, the role of other animal species in the epidemiological cycle of the disease, such as cattle, remains unclear. Therefore, the aim of the present study was to evaluate the occurrence of Leishmania spp. in 100 bovines (Bos taurus) from an area endemic for canine VL, using blood culture and molecular analysis. By the sequencing analysis, one sample showed 100% similarity with Leishmania infantum. The results provide the first case of L. infantum isolation in one bovine from the periurban areas of Bauru, state of São Paulo, Brazil.
Keywords: Blood culture; bovine; Brazil; Leishmania infantum; polymerase chain reaction